Rancangan Aplikasi Edukasi Alat Kesehatan Dan Alat Kedokteran Berbasis Android Dengan Metode Computer Assisted Instruction (CAI) - Romi Andrianto; Iwan Giri Waluyo; Savitri Savitri (JURIKOM (Jurnal Riset Komputer), 2022)
Medical science is a science that explores the handling of diseases carried out by health workers. The importance of the role of health workers today is based on data from the Ministry of Health, Indonesia still lacks health workers and it is hoped that a new generation will come who have broad knowledge, are intelligent, competitive and useful for public health. Basically, many prospective students who will enter medical education do not yet have knowledge about the use of medical devices, so education on the use of medical and medical devices needs to be carried out to provide insight to prospective health workers in the future. In this study, the author designed an application to provide education about medical devices commonly used in hospitals, both in terms of functions and how to use them for prospective students who are interested in majoring in health and medical sciences. The method in designing this system uses the Computer Assisted Instruction method. In its use, users can learn about medical and medical equipment according to their class, namely hospital health care and treatment, anesthesia equipment, teeth, eyes, ENT, radiology, cardiology, surgery, and several others. The author uses an expert review instrument in testing the validity and testing one to one to determine the practicality of using the application. Based on the results of the Expert Review, this application is declared valid based on the average value of the assessment results of media experts, design experts and evaluation experts with an average score of 4.0 so that this application category is declared valid. Furthermore, the results of the product practicality test through one to one testing were assessed by 3 respondents with an average value of 3.9 with practical criteria.